Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T.; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.